A Narrative Review of Entrepreneurship Education Assessment in Vocational High Schools in Pekanbaru - Putri Ramadani; Sumarno Sumarno; Fenny Trisnawati (International Journal of Educational Narratives, 2026)
Background. Entrepreneurship learning demands students’ ability to design, manage, and evaluate real business activities, requiring assessment systems capable of measuring entrepreneurial competence comprehensively and authentically. Purpose. This study analyzes the form, type, and instruments used in entrepreneurship assessment at Pekanbaru Vocational Schools, evaluates how holistically assessments reflect entrepreneurial competence, and examines the validity and reliability of instruments used. Method. A mixed-methods sequential explanatory design was employed across four vocational schools (SMK Negeri A–D, Pekanbaru). Data were collected via teacher questionnaires, documentation studies of learning tools, assessment results, and semi-structured interviews. Content validity was tested using Aiken’s V through expert judgment; criterion validity using Pearson Product Moment correlation both conducted only at two state schools, as private schools lacked independently compiled instrument documents. Reliability testing via Split-Half (Spearman-Brown) could not be implemented at any school due to unavailability of raw item-level score data, itself a substantive finding on assessment governance. Results. A significant decoupling emerged between high teacher questionnaire scores (84%–96%) and limited documentary evidence availability (0%). Content validity was satisfactory (Aiken’s V = 0.71–0.98). Criterion validity was confirmed only at SMKN A (r = 0.843; p = 0.000), while SMKN B was invalid (r = 0.010; p = 0.956) due to content misalignment. Conclusion. Entrepreneurship assessment practices at Pekanbaru vocational schools remain suboptimal. State schools face technical-pedagogical barriers; private schools face additional structural-managerial constraints preventing independent instrument documentation. Strengthening assessment data governance and instrument alignment is urgently needed.